Impact of Digital Marketing Strategies on Business Performance in the Digital Era - Lewar, Brigita; Anwarya, Winda; Alfian, Eva Reski (Scieclouds Publishing, 2024)
The rapid evolution of digital technologies has transformed marketing landscapes, creating new opportunities and challenges for businesses. This study investigates the impact of strategic digital marketing management on business performance, focusing on how various digital strategies enhance brand visibility, customer engagement, and sales performance. Utilizing a quantitative approach, a structured survey was administered to 300 marketing professionals and business managers across diverse industries. The survey, incorporating a Likert scale for measurement, explored the effectiveness of SEO, social media marketing, personalized content, targeted marketing, and PPC advertising. The analysis revealed significant correlations between these strategies and improved business outcomes. Descriptive and inferential statistics, including multiple regression analysis, Pearson correlation, and ANOVA, were employed to assess the relationships and effectiveness of the digital marketing tactics. The study's findings highlight the importance of integrating digital channels into a cohesive marketing strategy and the role of data-driven decisions in enhancing overall business performance. The research not only addresses existing literature gaps but also provides actionable insights for businesses to refine their digital marketing strategies. This study contributes to the understanding of how digital marketing innovations can be leveraged for competitive advantage in the digital age